2008
DOI: 10.5194/angeo-26-3955-2008
|View full text |Cite
|
Sign up to set email alerts
|

Escape of high-energy oxygen ions through magnetopause reconnection under northward IMF

Abstract: Abstract. During a storm recovery phase on 15 May 2005, the Geotail spacecraft repeatedly observed highenergy (>180 keV) oxygen ions in the dayside magnetosheath near the equatorial plane. We focused on the time period from 11:20 UT to 13:00 UT, when Geotail observed the oxygen ions and the interplanetary magnetic field (IMF) was constantly northward. The magnetic reconnection occurrence northward and duskward of Geotail is indicated by the Walén analysis and convective flows in the magnetopause boundary layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Observations of O + in the dayside magnetosheath during storm conditions were presented by Zong and Wilken (1998) and Zong et al (2001), who suggested the ions to be of ring-current origin, and referred to both flow along open field lines and finite gyroradius effects as possible escape mechanisms. Dayside observations of O + escape close to the equatorial plane correlated with a northward IMF were reported by Kasahara et al (2008), who showed that the escape took place along open field lines in relation to reconnection processes. Hirahara et al (1997), Marcucci et al (2004) and Taktakishvili et al (2007) are other examples of observations and studies of O + escape.…”
Section: Introductionmentioning
confidence: 68%
“…Observations of O + in the dayside magnetosheath during storm conditions were presented by Zong and Wilken (1998) and Zong et al (2001), who suggested the ions to be of ring-current origin, and referred to both flow along open field lines and finite gyroradius effects as possible escape mechanisms. Dayside observations of O + escape close to the equatorial plane correlated with a northward IMF were reported by Kasahara et al (2008), who showed that the escape took place along open field lines in relation to reconnection processes. Hirahara et al (1997), Marcucci et al (2004) and Taktakishvili et al (2007) are other examples of observations and studies of O + escape.…”
Section: Introductionmentioning
confidence: 68%
“…It has been shown that in their usual concentration (∼5%), alpha particles (He ++ ) in the solar wind and magnetosheath are probably not the primary cause of the subunity Walén slope (Puhl-Quinn and Scudder, 2000). On the other hand, oxygen ions (O + ) of magnetospheric origin, if abundant, may significantly affect the actual Alfvén speed (e.g., Kasahara et al, 2008).…”
Section: Walén Testmentioning
confidence: 99%
“…Therein, a significant fraction of cusp ions are sufficiently accelerated to escape through the magnetopause with a total escape flux of ∼7 · 10 24 s −1 . Possible processes responsible for the loss at the dayside are reconnection with the northward directed IMF (Kasahara et al 2008) or (2006) with observations of O + intensity at >274 keV measured by Cluster/RAPID in the plasma sheet at AE < 150 nT and AE > 300 nT, respectively the southward directed IMF , drift losses (mainly triggered by the solar wind dynamic pressure which changes the magnetopause shape; this is also applicable to the nightside plasma sheet) and due to the interaction with Pc 5 waves when the ion kinetic energy drops below the level required to overcome the convection potential, wherefore the ion is lost at the dayside magnetopause by sunward drift (Li et al 1993;Yang et al 2011). Supermagnetosonic plasma streams can lead to the escape of O + from the magnetosphere (Savin et al 2014).…”
Section: Bulk Properties and Global Modelsmentioning
confidence: 99%